THE ROLE OF CA 19.9 IN PREDICTING THE OPERABILITY OF CARCINOMA PANCREAS - JIJINRAJ P; RENJIN RP (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Adenocarcinoma of the pancreas remains a relatively incurable disease despite advances in surgical care. Approximately 25% of patients will be found to have unresectable tumors during surgery even though computed tomography (CT) has demonstrated that they are resectable. There is a controversy regarding the use of cancer antigen 19-9 (CA 19-9) to decide the resectability of pancreatic adenocarcinoma [1]. Our aim is to study the use of CA 19-9 in determining the operability of carcinoma pancreas [2]. Methods: This was a prospective study which included 69 patients and the study period was from December 2021 to December 2022. Data were collected from all patients with carcinoma of the pancreas who underwent surgical management. CA 19-9 levels were measured and recorded [3]. During surgery, the operative findings on resectability were documented and tabulated against corresponding CA 19-9 levels and contrast-enhanced CT (CECT) findings. Results: Of the 69 patients who were operated on, 38 patients had resectable tumors and underwent the Whipples procedure and 31 of them had non-resectable tumors and had to undergo palliative bypass procedures. Among the 31 patients whose tumors were non-resectable, only four were diagnosed non-resectable preoperatively with CECT, and the other 27 were found to be non-resectable only during surgery. That shows the relevance of this study. Of the 31 non-resectable cases, 14 (45.2%) patients had elevated CA 19-9 values of more than 501, and the rest 17 (54.8%) patients had low CA 19-9 values. Among the 38 resectable cases, 12 patients (31.6%) had elevated CA 19-9 more than 501, and 26 patients (68.4%) had low values. In conclusion, among non-resectable cases, 45.2% had raised CA 19-9, and among operable cases, 31.6% showed raised CA 19-9. Hence, CA 19-9 seems to be an insignificant predictor of tumor resectability [4]. Conclusion: It was found that the need for a pre-operative predictor for resectability of carcinoma pancreas is relevant while considering mortality and morbidity in operating carcinoma pancreas cases. On evaluating CA 19-9 as a pre-operative predictor, we found that CA 19-9 has no significant role as an indicator of local advancement or metastasis. Hence, we cannot consider CA 19-9 as a predictor of resectability of carcinoma pancreas preoperatively [5].